2017
DOI: 10.1063/1.4985296
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of AZO films for integrating optically transparent antennas with photovoltaics

Abstract: The importance of having an optimal material for fabricating Optically Transparent Antennas (OTAs) is crucial for designing highly efficient antennas that can be integrated with photovoltaics. Transparent Conductor Oxides are promising for OTA fabrication due to their capability of being simultaneously transparent at optical frequencies and conductive within the radio frequency (RF) range. Here in this study, thin aluminum and zinc oxide layers were co-sputtered onto Si and a polycrystalline photovoltaic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Patch antenna [4] Sputtering/spin-coating 2.4 Narrowband Patch antenna [5] Sputtering 10 Ultra-wideband Tapered slot antenna [6] Sputtering/spin-coating 2.5 Ultra-wideband Patch antenna [7] Spray pyrolysis 2.5/5 Narrowband Circular patch [8] Conductive fabric tissue 2.2-25 Ultra-wideband CPW-fed patch [9] Sputtering/spin-coating 2.45/5.8 Dual-band Sheikh et al investigated a transparent microstrip antenna with a fluorine-doped tin oxide patch, deposited using a spray pyrolysis technique on a Pyrex glass substrate, demonstrating high optical transmittance and low electrical surface resistance, and they compared the radiation properties with copper patch antenna counterparts [7]. The paper by Erfeng et al presents a flexible and transparent ultrawideband (UWB) antenna that uses a transparent conductive fabric tissue on a polydimethylsiloxane (PDMS) substrate, with promising potential for future wireless networks [8].…”
Section: Type Methods Frequency (Ghz) Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Patch antenna [4] Sputtering/spin-coating 2.4 Narrowband Patch antenna [5] Sputtering 10 Ultra-wideband Tapered slot antenna [6] Sputtering/spin-coating 2.5 Ultra-wideband Patch antenna [7] Spray pyrolysis 2.5/5 Narrowband Circular patch [8] Conductive fabric tissue 2.2-25 Ultra-wideband CPW-fed patch [9] Sputtering/spin-coating 2.45/5.8 Dual-band Sheikh et al investigated a transparent microstrip antenna with a fluorine-doped tin oxide patch, deposited using a spray pyrolysis technique on a Pyrex glass substrate, demonstrating high optical transmittance and low electrical surface resistance, and they compared the radiation properties with copper patch antenna counterparts [7]. The paper by Erfeng et al presents a flexible and transparent ultrawideband (UWB) antenna that uses a transparent conductive fabric tissue on a polydimethylsiloxane (PDMS) substrate, with promising potential for future wireless networks [8].…”
Section: Type Methods Frequency (Ghz) Performancementioning
confidence: 99%
“…Wu et al developed a transparent conducting film using an Aluminum Zinc Oxide (AZO)/Ag Nano Wires (AgNWs) composite and built a wide-band transparent antenna for Bluetooth communication using the RF magnetron sputtering deposition method [4]. Using a similar deposition method, Zamudio et al demonstrated the feasibility of using AZO as a transparent and conductive material for Optically Transparent Antenna (OTA) fabrication, which can be integrated with photovoltaics for a high efficiency [5]. Peter et al presented a transparent ultra-wideband antenna that can be integrated with photovoltaic solar panels, harvest RF energy, and operate in the frequency range from 2.2 to 12.1 GHz [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additional access points and signal repeaters embedded into the existing infrastructure help mitigate these issues through embedding transparent antennas into the windows by means of metallic meshes , /nanowires or transparent conductive oxides (TCOs). ,, The present article demonstrates the first TCO-based transparent antenna processed entirely by ALD. Optically transparent antennas based on both AZO and GZO have been previously demonstrated (comprehensive reviews on TCO-based antennas here ,, ). AZO antennas were fabricated to operate at 11 and 45 GHz, and a GZO antenna was fabricated to operate at 2.4 GHz.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 35 , 46 The present article demonstrates the first TCO-based transparent antenna processed entirely by ALD. Optically transparent antennas based on both AZO 47 and GZO 48 have been previously demonstrated (comprehensive reviews on TCO-based antennas here 28 , 49 , 50 ). AZO antennas were fabricated to operate at 11 and 45 GHz, and a GZO antenna was fabricated to operate at 2.4 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent conductive thin films are popular transparent conductors, which are extensively used in electronic industry for decades. Thin film conductors include the family of transparent conductive oxides (TCOs), such as indium‐tin‐oxide (ITO) [7], multi‐layered ITO (IZTO/Ag/IZTO) film [8], fluorine‐doped tin oxide [9], aluminium zinc‐oxide [10] and conductive polymers, such as silver‐coated polyester (AgHT) film [11]. Thin film conductors are associated with the trade‐off between their achievable optical transparency and electrical conductivity [12].…”
Section: Introductionmentioning
confidence: 99%